2013
DOI: 10.1142/s0218957713500103
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Complaints Among High School Teachers

Abstract: Musculoskeletal disorders represent one of the leading causes of occupational injury and disability in the developed and industrially developing countries. The prevalence of musculoskeletal disorders (MSDs) among Iranian high school teachers was determined by using Nordic questionnaires as the diagnostic tool. Data on MSDs were analyzed in 231 high school teachers. The survey was performed four times, twice every year. The MSDs were defined using three definitions, based on the frequency, duration and pain int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
(20 reference statements)
3
3
4
Order By: Relevance
“…A similar link has been found between female gender and LBP among school teachers in Brazil (OR: 1.54, 95% CI: 1.22-2.07)[ 11 ]. Similar findings were also documented in a study conducted in Iran where more female teachers reported lower back pain (77.0% vs 69.0%) in comparison to their male colleagues[ 24 ]. In a Chinese study of school teachers, the percentage of female teachers was higher than that of their male counterparts in reporting LBP (52.6% vs 45.1%, p < 0.01)[ 21 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A similar link has been found between female gender and LBP among school teachers in Brazil (OR: 1.54, 95% CI: 1.22-2.07)[ 11 ]. Similar findings were also documented in a study conducted in Iran where more female teachers reported lower back pain (77.0% vs 69.0%) in comparison to their male colleagues[ 24 ]. In a Chinese study of school teachers, the percentage of female teachers was higher than that of their male counterparts in reporting LBP (52.6% vs 45.1%, p < 0.01)[ 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…Parallels can be drawn to other studies where 53.3% of Filipino[ 19 ], 53.8% of Ethiopian[ 20 ] teachers and 59.2% of Chinese primary and secondary school teachers[ 21 ] reported having LBP. The prevalence of LBP found in this study was relatively lower than those reported in studies conducted among female secondary school Saudi (63.8%)[ 22 ], Indian (66.2%)[ 23 ], Iranian (71.9%)[ 24 ] and Turkish teachers (74.9%)[ 25 ]. A relatively high prevalence of LBP, 84.0%, was found among Slovenian physical education teachers in a previous study[ 8 ].…”
Section: Discussioncontrasting
confidence: 82%
“…5 This study has revealed that female 78% and male 57.5% reported with the prevalence of LBP. Low back problem in the current study was more than that in Saudi 63.8%, 9 Botswana 55.7%, 14 Turkish teachers 74.9%, 11 Iranian teachers in a previous study 39 and in another Turkish study 51.4%, 31 China 40.0%, 26 France 34.8% 34 and Japan 20.6%. 43 The results of this part of study were relatively lower than Slovenian physical education 84.0%.…”
Section: Discussioncontrasting
confidence: 48%
“…1 , 2 , 11 , 17 , 37 , 38 MSS, particularly low back pain, are common in the general population. Prevalence of low back pain as high, or higher, has been reported among other occupational groups including tomato trainers, 31 dental hygienists, 24 High school teachers, 29 sewage workers 14 and fishermen. 25 Findings of this study using CMDQ also showed that 51% of subjects (33% male, 18% female) reported lower back discomfort.…”
Section: Discussionmentioning
confidence: 94%